The hedging performance of foreign currency options and foreign currency futures: a comparison - Shanker, Latha; Chang, Jack S.K.; McMaster University, Faculty of Business (My University, 1984)
This paper is concerned with an empirical comparison of the hedging effectiveness of currency options and currency futures contracts, when each instrument is used to hedge against variations in the exchange rate o f the spot currency. The results of the paper indicate that if the hedger were interested in minimizing risk alone, futures con tracts performed better than the corresponding options contacts. How ever, if the hedger were interested in minimizing the risk of a port folio of the spot currency and the hedging instrument for a given level of expected return, then the currency option performed better than the corresponding currency futures contract.
15, 7 leaves : ; Includes bibliographical references (leaves 14-15). ; Cover title.;"March, 1984".
Keywords: Foreign exchange market Foreign exchange futures Hedging (Finance) Options (Finance)